2022
DOI: 10.1158/1078-0432.ccr-21-4097
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Nanobody-Derived Fratricide-Resistant CD7-CAR T-cell Therapy for Patients with Relapsed and Refractory T-cell Acute Lymphoblastic Leukemia/Lymphoma

Abstract: Purpose: Since CD7 may represent a potent target for T-lymphoblastic leukemia/lymphoma (T-ALL/LBL) immunotherapy, this study aimed to investigate safety and efficacy of autologous CD7-chimeric antigen receptor (CAR) T cells in relapsed and refractory (R/R) T-ALL/LBL patients, as well as its manufacturing feasibility. Experimental Design: Preclinical phase was conducted in NPG{trade mark, serif} mice injected with Luc+ GFP+CCRF-CEM cells. Open label phase I clinical trial (NCT04004637) enrolled patients with R/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Expect for these common complications, hematological toxicities, HLH, infections and T cell aplasia also played a prominent role in anti-CD7 CAR-T therapies. Although hematological toxicities were signi cant, our data was broadly consistent with other anti-CD7 CAR-T studies (19)(20)(21)(22). CD34 + stem cell infusion and transplantation could effectively restore patients' bone marrow hematopoietic function after multiple lines of treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Expect for these common complications, hematological toxicities, HLH, infections and T cell aplasia also played a prominent role in anti-CD7 CAR-T therapies. Although hematological toxicities were signi cant, our data was broadly consistent with other anti-CD7 CAR-T studies (19)(20)(21)(22). CD34 + stem cell infusion and transplantation could effectively restore patients' bone marrow hematopoietic function after multiple lines of treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, CAR-T cells targeting CD7 have the potential to eliminate tumor cells, but also holds the risk to kill normal T and CAR-T cells. Since CD7 is proven non-essential for T cell development or function (17,18), several strategies including CRISPR-Cas9, natural selection, and endoplasmic reticulum retention, have been developed to block CD7 expression on CAR-T cells (19)(20)(21)(22). By adding a vector containing a CD7-binding domain fused to an endoplasmic reticulum retention signal domain, CD7 tra cking to the cell surface was restrained, thus avoiding fratricide among anti-CD7 CAR-T cells (22).…”
Section: Introductionmentioning
confidence: 99%
“…A study found that CD7 CAR-T cells could effectively eradicate CD7+ AML cell lines (GDM-1 and Kasumi-3), primary CD7+ AML, and colony-forming cells in a xenograft mice model but did not affect the normal cells in bone marrow [ 113 ]. Besides, nanobody-based fratricide-resistant CD7-CAR T cells demonstrated a favorable and durable antitumor response in r/r T-ALL/LBL with tolerable toxicity, warranting further studies in highly aggressive CD7-positive malignancies [ 114 ]. However, since T cells express CD7, T cell self-mutilation is an issue to be considered for CD7 CAR-T cell therapy.…”
Section: Haematologic Cancersmentioning
confidence: 99%
“… 116 (4) Novel approaches to fratricide, such as using nanobody-derived CAR-T-cells or naturally selected fratricide-resistant CAR-T-cells, have demonstrated superiority in the treatment of CD7+ malignancy ( Figure 4 ). 34 , 117 They provided a new way to overcome fratricide excluding gene editing, which may help maintain the natural characteristics of cells and enhance the safety as well as efficacy. Liu et al cultivated anti-CD7 CAR-T-cells in vitro and selected cells that survived after fratricidal natural selection.…”
Section: Solutions To Overcome the Current Challenges And Enhance Eff...mentioning
confidence: 99%
“…These researchers demonstrated that nanobody-derived CAR-T-cells can avoid fratricide and have a great antitumor effect. 119 Zhang et al 117 reported a clinical trial with this kind of anti-CD7 CAR-T-cells. Of the eight patients enrolled in the trial, the CR rate at 3 months was 87.5% (7/8), and no life-threatening CRS or ICANS was observed.…”
Section: Solutions To Overcome the Current Challenges And Enhance Eff...mentioning
confidence: 99%